Crafting Innovative Places for Australia's Knowledge Economy - Blakely, Edward J.; Hu, Richard (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This book integrates planning, policy, economics, and urban design into an approach to crafting innovative places. Exploring new paradigms of innovative places under the framework of globalisation, urbanisation, and new technology, it argues against state-centric policies to innovation and focuses on how a globalized approach can shape innovative capacity and competitiveness. It notably situates the innovative place making paradigm in a broader context of globalisation, urbanisation, the knowledge economy and technological advancement, and employs an international perspective that includes a wide range of case studies from America, Europe, Asia, and Australia. Developing a co-design and co-creation paradigm that integrates governments, the private sector and the community into shared understanding and collaborative action in crafting innovative places, it discusses place-based innovation in Australian context to inform policy making and planning, and to contribute to policy debates onprograms of smart cities and communities. .